Heat transfer enhancement in microchannels with cross-flow synthetic jets - Chandratilleke, Tilak; Jagannatha, Deepak; Narayanaswamy, Ramesh (Elsevier, 2010)
This paper examines the effectiveness of using a pulsating cross-flow fluid jet for thermal enhancement in a microchannel. The proposed technique uses a novel flow pulsing mechanism termed “synthetic jet” that injects into the microchannel a high-frequency fluid jet with a zero-net-mass flow through the jet orifice. The microchannel flow interacted by the pulsed jet is modelled as a two-dimensional finite volume simulation with unsteady Reynolds-averaged Navier–Stokes equations while using the Shear-Stress-Transport (SST) k–ω turbulence model to account for fluid turbulence. For a range of conditions, the special characteristics of this periodically interrupted flow are identified while predicting the associated convective heat transfer rates. Results indicate that the pulsating jet leads to outstanding thermal performance in the microchannel increasing its heat dissipation by about 4.3 times compared to a channel without jet interaction within the tested parametric range. The degree of enhancement is first seen to grow gently and then rather rapidly beyond a certain flow condition to reach a steady value. The proposed strategy has the unique intrinsic ability to generate outstanding degree of thermal enhancement in a microchannel without increasing its flow pressure drop. The technique is envisaged to have application potential in miniature electronic devices where localised cooling is desired over a base heat dissipation load.